Systematic Consideration of Parameter Uncertainty and Variability in Probabilistic Species Sensitivity Distributions. (13th December 2019) - Wigger, Henning; Kawecki, Delphine; Nowack, Bernd; Adam, Véronique
ABSTRACT: The calculation of a species sensitivity distribution (SSD) is a commonly accepted approach to derive the predicted no‐effect concentration (PNEC) of a substance in the context of environmental risk assessment. The SSD approach usually is data demanding and incorporates a large number of ecotoxicological values from different experimental studies. The probabilistic SSD (PSSD) approach is able to fully consider the variability between different exposure conditions and material types, which is of great importance when constructing an SSD for any chemical, especially for nanomaterials. The aim of our work was to further develop the PSSD approach by implementing methods to better consider the uncertainty and variability of the input data. We incorporated probabilistic elements to consider the uncertainty associated with uncertainty factors by using probability distributions instead of single values. The new PSSD method (named "PSSD+") computes 10 000 PSSDs based on a Monte Carlo routine. For each PSSD calculated, the hazardous concentration for 5% of species (HC5 ) was extracted to provide a PNEC distribution based on all data available and their associated uncertainty. The PSSD+ approach also includes the option to consider a species weighting according to a typically constituted biome. We applied this PSSD+ approach to a previously published data set on C nanotubes and Ag nanoparticles. The evaluation of the uncertainty factor distributions and species weighting have shown that the proposed PSSD method is robust with respect to the calculation of the PNEC value. Furthermore, we demonstrated that the PSSD+ can handle both small and more comprehensive data sets because the PNEC distributions are a close representation of the data available. Finally, the sensitivity testing toward data set variations showed that the maximum variation of the mean PNEC was of a factor of about 2, so that the method is relatively insensitive to missing data points as long as the most sensitive species is included. Integr Environ Assess Manag 2020;16:211–222. © 2019 SETAC KEY POINTS: We incorporated probabilistic elements in species sensitivity distributions (SSDs) to consider the uncertainty associated with uncertainty factors by using probability distributions instead of single values and species weighting according to a typical biome. The HC5 extraction of all calculated probabilistic species sensitivity distributions (PSSDs) yields a predicted no‐effect concentration (PNEC) distribution based on all data available and their associated uncertainty without omitting data points for species due to data aggregation. The new PSSD+ approach avoids the fitting problem of conventional SSDs and can be used for small and bigger data sets.